Eating disorders and non-suicidal self-injury: Structural equation modelling of a conceptual model - Vieira, Ana Isabel (2018)
Evidence suggests several risk factors for both eating disorders (ED) and nonsuicidal self‐injury (NSSI), but the relationships between these factors are not well understood. Considering our previous work and a conceptual model, this cross‐sectional study aimed to assess the relationships among distal and proximal factors for the presence of NSSI in ED. We assessed 245 ED patients with the Oxford Risk Factor Interview for ED. Structural equation modelling revealed that both distal and proximal factors were related to the presence of NSSI in ED, disclosing a mediating role of the proximal factors. Stressful life events mediated the relationship between childhood sexual abuse, peer aggres-sion, and both ED and NSSI. Childhood physical abuse was related to ED and NSSI via substance use, negative self‐evaluation, and suicide attempts. Find- ings provided support for the conceptual model and highlight the possible mechanisms by which psychoso cial factors may lead to ED and NSSI.